Where histories reside : India as filmed space - Jaikumar, Priya, 1967- (Duke University Press, 2019)
Priya Jaikumar examines seven decades of films shot on location in India to show how attending to filmed space reveals alternative timelines and histories of cinema as well as the myriad ways cinema constructs India as a place.